Humanitarians at war : the Red Cross in the shadow of the Holocaust - Steinacher, Gerald (2017)
How the International Committee of the Red Cross emerged triumphant from the dark days of World War II - to forge a new identity and a new role in the post-1945 world. The intriguing and remarkable story of one of the world's oldest, most prominent, and most revered aid institutions - and how it survived its ambiguous relationship with the Nazis. From the brink of dissolution in 1945 to the triumph of the Geneva Conventions in 1949, a tale encompassing the Nuremberg Trials, runaway Nazis, and furious battles with Communist critics on the eve of the Cold War. Torn between defending Swiss neutrality and battling Communist critics in the early Cold War, the Red Cross leadership in Geneva emerged from the world war with a new commitment to protecting civilians caught in the crossfire of conflict. Yet they did so while interfering with Allied de-nazification efforts in Germany and elsewhere, and coming to the defence of former Nazis at the Nuremberg Trials. Not least, they provided the tools for many of Hitler's former henchmen, notorious figures such as Joseph Mengele and Adolf Eichmann, to slip out of Europe and escape prosecution - behaviour which did little to silence those critics in the Allied powers who unfavourably compared the 'shabby' neutrality of the Swiss with the 'good neutrality' of the Swedes, their eager rivals for leadership in international humanitarian initiatives